Optimization of Electrical Energy Generation Systems in the Mini-grids of Southern Algeria - Souria DAHMANI; Aïssa MOUHOUBI (المجلة الدولية للأداء الاقتصادي, 2023)
The objective of this paper is to review the electrification modes associated with the Great Algerian South Networks (GSN). The study focuses on the conceptualization of the GSN through the dimensioning of mini-grids. Given the remoteness and difficulties of fuel supply, a series of reforms have been undertaken to promote the energy transition and ensure the development of these regions through the realization of hybrid systems in order to reduce the dependence on fossil fuel sources by ensuring energy savings.